2019
DOI: 10.1136/neurintsurg-2018-014490
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of coil embolization in posterior and anterior communicating artery aneurysms

Abstract: BackgroundRecanalization rates after coil embolization are known to be higher in cerebral aneurysms of the posterior (vs anterior) circulation. Although often grouped with anterior lesions, aneurysms of the posterior communicating artery (PcoA) may nevertheless behave differently.ObjectiveWe performed a comparative analysis to explore differences in recanalization rates of PcoA and anterior communicating artery (AcoA) aneurysms, both integral to the circle of Willis.MethodsBetween October 2012 and July 2017, 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 28 publications
3
10
0
Order By: Relevance
“…The ISAT study has shown that PcoA aneurysms are subjected to recoiling procedures more often than aneurysms at other sites (p=0.03) 17. Another study aimed at differing rates of recanalization in aneurysms of the anterior communicating artery (AcoA) and PcoA has also confirmed more frequent recanalization in the latter, likely due to posterior circulatory behavior 8. There were similar results in our study.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The ISAT study has shown that PcoA aneurysms are subjected to recoiling procedures more often than aneurysms at other sites (p=0.03) 17. Another study aimed at differing rates of recanalization in aneurysms of the anterior communicating artery (AcoA) and PcoA has also confirmed more frequent recanalization in the latter, likely due to posterior circulatory behavior 8. There were similar results in our study.…”
Section: Discussionsupporting
confidence: 87%
“…The posterior communicating artery (PcoA) provides a crucial link between the anterior and posterior cerebral circulation and is particularly important clinically, accounting for approximately 25% of all intracranial aneurysms 7. Furthermore, there is evidence that recanalization after coil embolization is frequent in this location 1 8. The hemodynamic stress imposed on coiled aneurysms of the PcoA is clearly influenced by flow from the internal carotid artery (ICA), and anatomic variants of the PcoA may play a role as well.…”
Section: Introductionmentioning
confidence: 99%
“…The incidence rates of fPCA and variation of the unilateral A1 segment in this study were 27.9% (41/147) and 64.2% (43/67), respectively, which are similar to those seen in other studies (30-40% and >60%) (3,6). Prior studies have suggested that PcomA aneurysms are more likely to recur than AcomA aneurysms (37.2% versus 25.0%, P=0.259, and 23.0% versus 12.2%, P<0.01) (2,12). However, these studies appeared to have neglected P1 or A1 segment variation factors that could increase these aneurysms' recanalization rates.…”
Section: Discussionsupporting
confidence: 89%
“…From January 2013 to January 2020, patients with either PcomA aneurysms or AcomA aneurysms at our center were included in this study. fPCA can be divided into 2 types: partial fPCA and full fPCA (8), and variation of the A1 segment can likewise be divided into 2 types: Al segment hypoplasia and unilateral absent A1 segment (2).…”
Section: Patients and Datamentioning
confidence: 99%
See 1 more Smart Citation